CROWDSOURCING DATA PERUBAHAN GARIS PANTAI DI KOTA PADANG MELALUI WEB-GIS - Khairul Nizam; arie Yulfa (JURNAL BUANA, 2022)
The dynamics of changing shorelines that always change from time to time are often too late to be known due to limited facilities and media in conveying the latest information. Crowdsourcing is an online distributed problem solving that utilizes the online intelligence of the community that serves specific organizational goals (C.Abraham, 2013). Crowdsourcing is a method in collecting data in the field by involving/participating internet users in collecting information. The limitations of map visual media in providing information became the background for the creation of a Web-GIS called Shoreline Alert. Shoreline Alert is used as a participatory and real-time forum in collecting and delivering data on shoreline changes that occur in the field. The results of using Shoreline Alert as a forum for collecting information are considered faster and more effective, because it shortens the time for information in the field to stakeholders related to the help of the internet network so that it can produce policies that are fast and on target to deal with the phenomenon of shoreline changes that occur in the field.